Altman Z Score Method for Predicting Bankruptcy in Kompas 100 Index Companies - Herman Somantri; M. Kohar Mudzakar (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
This study aims to predict bankruptcy in companies indexed in Kompas 100. The research does on 30 sample companies based on a purposive sampling technique for 2019 – 2021. The research does use explanatory and descriptive investigations. The results showed that 18 companies met the healthy category in 2019, 15 in 2020, and 18 in 2021. A gray area category, 2019, 10 companies; 2020, 9 companies. And 2021, 8 companies. For the bankruptcy category, in 2019, 2 companies. In 2020, 6 companies, and in 2021, 4 companies.